Improving Writing Skill with Questioning: A Path on Critical Thinking Skill - Rika Riwayatiningsih (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2019)
Driving students to be a critical thinker in their process of writing is hardly a challenge. As an effective process of writing depend on how well they develop their critical thinking skills, helping them build the critical thinking in writing is considered as a way to make a correct judgment independently and create an environment that raises their best writing. The current study attempts to investigate whether the use of questions could generate students’ critical thinking in their writing process. The participants were 38 English Department students who encountered argumentative writing class in University degree. The subjects were assigned into a mix method on a quasi- experimental study involving pretest - posttest with some features of semi structured interview to know their level of satisfaction from the gained score. The results of the study showed that the significance of exploring questions in helping students’ critical thinking for meaningful learning, especially in the connectivity and coherency of their writing product and also the flow of the sentences. Moreover, the students are being actively involved in meaningful communicative language during the process of writing. This good engagement contributes for the positive classroom management.